The Development of Halal Tourism and its Impact on Economic Growth in North Sumatra - Nirmadarningsih Hiya; Shamir Hashim Syarif; Sabaruddin Chaniago; Nasib Nasib; Tennisya Febriyanti Suardi (Journal of Economics and Business (JECOMBI), 2026)
This study examines the effect of halal tourism development on economic growth in North Sumatra during the 2020–2025 period. Halal tourism development is represented by the growth of halal certification and the accommodation and food service sector, while economic growth is measured using the growth rate of Gross Regional Domestic Product at constant prices. The study employed a quantitative descriptive-associative design using secondary data from 33 regencies and municipalities, resulting in 198 observations. Data obtained from Statistics Indonesia and the Halal Product Assurance Organising Agency were analysed using SPSS through multiple linear regression, partial and simultaneous tests, and the coefficient of determination. The findings indicate that halal certification growth and the growth of the accommodation and food service sector have positive and statistically significant effects on economic growth. Simultaneously, both variables significantly influence regional economic growth and explain 64.3% of its variation. These findings highlight the importance of strengthening halal certification and tourism-supporting services to promote regional economic development.